Performance analysis of penalty area entrances of a South African men's professional football team - Engelbrecht, W. P. (University Stellenbosch, 2010)
The purpose of the study was to analyse the penalty area entrances of a team competing in the Premier Soccer League (PSL) in South Africa. Ten home matches of the team were analysed making use of a category set designed for the study. The main areas of analysis included the point of final action before the ball entered the penalty area, the part of the penalty area at which the entrance occurred, the method of entrance, the number of completed passes within the area, and the outcome of the entrance as well as the reason for the outcome. The results revealed that the team entered the penalty area on average 59.4 times per match and scored a goal on every 37.4 penalty area entrances. The ball being taken away by the opponents was the outcome that occurred most frequently within the penalty area (42.1% of all entries), and was largely due to interceptions by the defending team (20.7%). The next most commonly occurring event was the ball being given away by the attacking team (22.4% of all entries) and was largely as a result of the poor passing (20%). The results revealed that in order for the team to improve their ability to convert their attacking opportunities into goals, improvement of technical execution in particular passing and shooting within the critical areas of the field must be established. The results have implications for the use of performance analysis for professional teams as support for the coaching process.